HEALTH RISK ASSESSMENTS OF HEAVY METALS OF PERNA VIRIDIS FROM BANYUURIP WATERS IN UJUNG PANGKAH, GRESIK - Rayyan, Muhammad Fathur; Yona, Defri; Sari, Syarifah Hikmah Julinda (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2019)
Banyuurip is one of villages in Ujung Pangkah District, Gresik with high aquaculture activities of Perna viridis. Green mussels are highly produced in that area, however Banyuurip waters also has potential risk of heavy metals pollution. Therefore, this research was conducted to understand the concentrations of Fe and Zn in the sediments and in the Green Mussels. The heavy metals concentration will be used to analyze Bio Concentration Factor (BCF) and Human Health Risk Assessments (HHRA). A total about 45 P. viridis populations were collected from 3 sites in Banyuurip waters. In order to obtain a representative sample at each site, 15 populations of Green Mussels with similar shell lengths and bottom sediment were collected. Mussel’s tissue and bottom sediment were analyzed using AAS (AAnalyst700) to determine the concentrations of Fe and Zn. The concentrations of Fe were found almost similar with the concentrations of Zn in P. viridis within the range of Fe = 3.10 – 5.25 mg.kg-1 and Zn = 3.91 - 4.67 mg.kg-1. BCF (o-s) of Fe in P. viridis is lower than the BCF (o-s) of Zn, because the concentrations of Fe in the mussels were less than the concentrations in the sediments. According to the Target Hazard Quotients (THQ) values (THQ < 1), both heavy metals are not likely causing negative health effects for human during lifetime. However, Estimated Daily Intakes (EDI) values are above Provisional Tolerable Daily Intakes (PTDI) standard means it can cause negative effects due to daily consumption (EDI > PTDI).